Comparing various scoring system for predicting overall survival according to treatment modalities in hepatocellular carcinoma focused on Platelet-albumin-bilirubin (PALBI) and albumin-bilirubin (ALBI) grade: A nationwide cohort study - Lee, Soon Kyu; Song, Myeong Jun; Kim, Seok Hwan; Park, Misun (PloS one, 2019)
We evaluated the ability of various grading scales including platelet-albumin-bilirubin (PALBI) and albumin-bilirubin (ALBI) grades to predict overall survival (OS) according to treatment modality in patients with hepatocellular carcinoma (HCC). The cohort of 6,669 patients with HCC was selected randomly from the 2008-2012 national cohort of the Korean Central Cancer Registry. The OS of 6,507 of these patients was evaluated using the Child-Turcotte-Pugh (CTP) class, Model for End-stage Liver Disease (MELD) score, and ALBI and PALBI grades. The patient's mean age was 59.7 years. The most patients were hepatitis B virus (63.4%) and CTP class A (71.8%). The median OS durations of PALBI grade1 (38.4%), grade2 (33.2%), and grade3 (28.4%) patients were 81, 30, and 5 months, respectively (P<0.001). The PALBI grade had a larger area under the receiver operator characteristic curve (AUC) than did the CTP class, MELD score, and ALBI grade (overall AUC: 0.675 vs. 0.633, 0.645, and 0.642, respectively; P < 0.001). Moreover, the PALBI and ALBI grades enabled sub-classification of CTP A patients (P < 0.001). In a multivariate analysis, the PALBI and ALBI grades were significant risk factors for OS (P < 0.05). According to treatment modality, the PALBI grade was predictive of OS in patients receiving transarterial chemoembolization or supportive care. The ALBI grade was predictive of OS in patients undergoing surgical resection or radiofrequency ablation. The PALBI and ALBI grades are more reliable for accessing liver function and predicting OS in patients with HCC. Moreover, according to treatment modality, appropriate use of the ALBI and PALBI grades will enable accurate determination of the prognosis of patients with HCC.